Role of nonproductive tillers as transient sinks of assimilates in wheat - Fioreze S.L. (2020)
© 2020, Agronomic Institute of Campinas. All rights reserved.Although source–sink relationships in wheat are well studied, the performance of tillers as transient sinks is still unclear, especially under stress conditions. Thus, this work aimed to study the yield relationships of wheat stems in contrasting genotypes as affected by tiller treatment under stress conditions. Two experiments were conducted under greenhouse conditions using BRS Guamirim (high tillering) and BRS Parrudo (low tillering) wheat cultivars. Four tillering treatments were applied on late tillers in the first growing season (2016) and three in the second (2017): (i) free-tillering, (ii) detillering, (iii) physical suppression (only in the first season) and (iv) “spikes removal”. The main stem and the first four emitted tillers were considered as primary tillers. Plants were submitted to drought (2016) and defoliation stress (2017) at preanthesis. Intraspecific competition among tillers increased under drought stress conditions and decreased the plant performance. Nonproductive late tillers do not improve the performance of primary tillers of wheat plants under drought stress, mainly in high-tillering cultivars. The reduction on the thousand grain weight of only ‘Parrudo’ detillered plants indicates that assimilate remobilization from late tillers to primary tillers and main stem seems to be more effective in low-tillering cultivars.